SUSTAINABLE DEVELOPMENT AT BINTAN ISLAND - Vitrisia Klastika (Jurnal Ilmiah MTG, 2009)
Indonesia has a great potential in the natural resources, especially Titan Mining in one of the beautiful islands, Bintan Island. Unfortunately, this potential is not encouraged with a good attitude of the Indonesia people. The hi-tech technology can not make Bintan Island become better; sustainable in its economy was stuck because the area has been damaged by mining irresponsibility. It needs participation from all people and both government organizations and non government organizations to make a better life in Bintan Island.